Lenin v 1917 godu. Vospominanija. [Pri učast. L.N. Stali, F.I. Drabkinoj, I.P. Flerovskogo i dr. Sost. A.P. Žukova, E.K. Minina, R.M. Savitskaja i dr.]
S ill-mi, prt-mi i ukaz. Institut Marksizma-Leninizma pri CK KPSS.